Core Spreading Vortex Method for Simulating 3D Flows Around Bluff Bodies - Zuhal, Lavi Rizki; Dung, Duong V.; Sepnov, Alex J.; Muhammad, Hari (ITB Journal Publisher, LPPM ITB, 2014)
This paper presents the development of core spreading vortex element method, which is a mesh-free method, for simulating 3D viscous flow over bluff bodies. The developed method simulates external flow around complex geometry by tracking local velocities and vorticities of particles introduced within the fluid domain. The viscous effect is modeled using core spreading method coupled with the splitting spatial adaption scheme, and a smoothing interpolation scheme for overlapping issue and population control, respectively. The particleâs velocity is calculated using Biot-Savart formulation. To accelerate computation, Fast Multipole Method (FMM) is employed. The solver is validated, for both unbounded and bounded flows at low Reynolds numbers, using a number of benchmark problems. For unbounded case, simulation of the collision of two vortex rings was performed. To test the performance of the method in simulating bounded flow problem, simulation of flow around a sphere was carried out. The results are found to be in good agreement with those reported in literatures and also simulations using other diffusion model.